The Relationship Between a Healthy Lifestyle and A Person's Social Approach - Sh.Q. Alimov (Zien Journals, 2021)
In this article, the author analyzes the interrelationship between the personal example of student youth, their healthy lifestyle, and their social adaptation during their university years.
Keywords: Healthy lifestyle; personality; social adaptation; health